Multifunctional nanocatalysts for tandem reactions: a leap toward sustainability - Jagadeesan, Dinesh (Applied Catalysis A-General, 2016)
Design of new multifunctional nanocatalysts is a hot area of research that aims to introduce multiple types of active sites on a single nanocatalyst. Multifunctional nanocatalysts are useful to carry out a multi-step reaction requiring same or different active sites in a single pot. Such catalysts must possess the active sites at spatially distinct locations to avoid neutralization but yet remain active independently or through cooperative actions. The necessity of nanostructuring the active sites have emerged as the key point in a successful design of the catalysts. The review covers the progress in this area of research done in the last five years. It includes the classification of catalysts based on active sites and structure of active sites at the nanoscale. The review covers exhaustively with 250+ references and ample examples to present the concept succinctly. The review covers the evolution of multifunctional catalysts from the perspective of materials chemistry. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Multifunctional nanocatalysts; Nanostructured materials; Tandem reactions